Obtaining the optimum efficiency electrical energy under Diyarbakir conditions using solar tracking system involving PV panel - (:unkn) unknown (My University, 2012)
In this study, the electromechanical two-axis solar tracking system is designed and tested. The mechanism of the system is controlled with open-loop system and the system directed by microcontroller to the position of the sun to get the maximum electrical energy efficiency. The difference between the mechanical and fixed system is compared experimentally considering the result of work. A fixed system is established inclined 370 to the south to be able to compare. It is realized that the energy measured from the solar tracking system that moves two axes is significantly much more than the one of fixed system. According to the results, the measured values under Diyarbakir conditions are up to 46.93% during the winter months and on average up to 32.84% (as annually) which shows an important increase in energy. © Sila Science.
Keywords: Microcontroller; Photovoltaic; Solar energy; Two axes sun tracking